The Effect of Using Flipped Classroom Strategy on the Second Grade Student’s Achievement in Arabic Subject in Dayr-Alla Directorate - Al-Yasjeen, Nawal Ghassan Abdelrazaq (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the effect of using flipped classroom strategy on the second grade student’s achievement in Arabic subject in Dayr-Alla directorate, the study used the qusai- experimental approach. An achievement test was developed it consist of (20) paragraph and their validity and reliability were confirmed, the sample of study consisted from (30) female and male student they distributed to control group they were taught in the usual way and experimental group they were taught in the flipped classroom strategy way. However, the study showed there was statistical difference at the level (α≤0.05) in the average of the educational achievement test attributed to the teaching strategy, in favor of the member of the experimental group, the finding also showed there weren’t any differences at the level (α≤0.05) in the average of the educational achievement test attributed to the sex of students.